2011
DOI: 10.1016/j.tsf.2011.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis and process stability in reactive high power impulse magnetron sputtering of metal oxides

Abstract: In the further development of reactive sputter deposition, strategies which allow for stabilization of the transition zone between the metallic and compound modes, elimination of the process hysteresis, and increase of the deposition rate, are of particular interest. In this study, the hysteresis behavior and the characteristics of the transition zone during reactive high power impulse magnetron sputtering (HiPIMS) of Al and Ce targets in an Ar-O 2 atmosphere as a function of the pulsing frequency and the pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 25 publications
2
48
0
Order By: Relevance
“…The stabilization of the transition zone allows for deposition of stoichiometric films at a lower target coverage when compared to the compound mode in DCMS. 30,73,84 This has been shown to result in deposition rates similar 30 or up to two times higher 84 than those obtained by DCMS. It is worth mentioning that all the studies on reactive HiPIMS have been performed in small-size laboratorial scale deposition systems.…”
Section: F Reactive Hipimsmentioning
confidence: 82%
See 1 more Smart Citation
“…The stabilization of the transition zone allows for deposition of stoichiometric films at a lower target coverage when compared to the compound mode in DCMS. 30,73,84 This has been shown to result in deposition rates similar 30 or up to two times higher 84 than those obtained by DCMS. It is worth mentioning that all the studies on reactive HiPIMS have been performed in small-size laboratorial scale deposition systems.…”
Section: F Reactive Hipimsmentioning
confidence: 82%
“…At the same time there is a tradeoff with the degree of ionization, where the highest reported values are found for the 20 ls pulses. 28 It is also reported that shorter pulses have beneficial consequences for reactive HiPIMS processes, 73 which are discussed in more detail in Section II F.…”
Section: E Pulse Configurationmentioning
confidence: 98%
“…At this frequency, the duty cycle was 35% which is substantially higher than that of the typical values used in HiPIMS. Furthermore, the power density within the pulse was low and the condition corresponded to mid-frequency reactive magnetron sputtering [9]. These examples from literature show that with reactive HiPIMS process, under optimized experimental conditions, hysteresis can be suppressed/eliminated.…”
Section: Introductionmentioning
confidence: 85%
“…We have previously found that there is a range of pulse repetition frequencies at which a HiPIMS process can reduce or completely remove the hysteresis [9]. The range of frequency used was from 1 kHz to 10 kHz where the optimum frequencies were found to be between 2 and 4 kHz for the Al-O system, but are likely to vary depending on various process conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation